Design for the other 90%. - Smithsonian Institution (New York : Cooper-Hewitt, 2007)
Cooper-Hewitt, National Design Museum exhibition catalogue for the show Design for the other 90%. Of the world's total population of 6.5 billion, close to 5.83 billion, or 90%, have little or no access to most of the products and services many of us take for granted; in fact nearly half do not have regular access to food, clean water, or shelter. Design for the other 90% explores more than thirty projects which reflect the growing movement among designers, engineers, students and professors, architects, and social entrepreneurs to design low-cost solutions for this other 90%. Through partnerships both local and global, individuals and organizations around the United States and throughout the world are inventing unique ways to provide better access to food, water, shelter, health, education, and energy to those who most need them.
Published on the occasion of the exhibition at Cooper-Hewitt, National Design Museum, Smithsonian Institution, May 4 - September 23, 2007